High pressure study of sodium trihydride - Marqueño, Tomas; Kuzovnikov, Mikhail A.; Osmond, Israel; Dalladay-Simpson, Phillip; Hermann, Andreas; Howie, Ross T.; Peña-Alvarez, Miriam (Frontiers in Chemistry, 2024)
The reactivity between NaH and H2 has been investigated through a series of high-temperature experiments up to pressures of 78 GPa in diamond anvil cells combined with first principles calculations. Powder X-ray diffraction measurements show that heating NaH in an excess of H2 to temperatures around 2000 K above 27 GPa yields sodium trihydride (NaH3), which adopts an orthorhombic structure (space group Cmcm). Raman spectroscopy measurements indicate that NaH3 hosts quasi-molecular hydrogen (H2δ−) within a NaH lattice, with the H2δ− stretching mode downshifted compared to pure H2 (Δν ∼−120 cm−1 at 50 GPa). NaH3 is stable under room temperature compression to at least 78 GPa, and exhibits remarkable P-T stability, decomposing at pressures below 18 GPa. Contrary to previous experimental and theoretical studies, heating NaH (or NaH3) in excess H2 between 27 and 75 GPa does not promote further hydrogenation to form sodium polyhydrides other than NaH3.